Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.3* The Natural Exponential Function - 6.3* Exercises - Page 453: 54


The equation of tangent at (0, 1) is $y=e$.

Work Step by Step

The slope of the tangent can be calculated by taking first derivative of the function $y=\frac{e^{x}}{x}$ $y'=\frac{xe^{x}-e^{x}}{x^{2}}=\frac{e^{x}(x-1)}{x^{2}}$ Slope of the tangent at $(1,e)$ is given as follows: $y'|_{(1,e)}=0$ The equation of tangent at (0, 1) is $(y-y_{1})=m(x-x_{1})$ Here $ m=0$ $(y-e)=0(x-1)$ Hence, $y=e$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.